Commodity futures - A study of online trading in rubber - Anu S Nair (Department of Rural Banking and Finance Management, College of Co operation and Management, 2007)
The present study entitled “COMMODITY FUTURES A STUDY OF ONLINE TRADING IN RUBBER” was conducted with the following objectives. 1) To examine the price movements of rubber futures through National Multi Commodity Exchange of India Ltd. (NMCE). 2) To assess the impact of futures trading on farming decisions of rubber farmers; and 3) To identify the determinants of online trading by rubber farmers. Primary and secondary data have been used for the study. Daily data of rubber futures in NMCE and the corresponding spot prices were collected from the website of NMCE. The data regarding the area production, yield, export, import, major producing countries and major consuming countries were collected from the souvenir of publications of Rubber Board, Economic Survey and website of tire review. Primary data to analyse the impact of futures trading and to identify the determinants were collected using a structured interview schedule. The sample respondents constituted 33 trading farmers from the districts of Kottayam, Palakkad and Thrissur and another group of 33 non-trading farmers from the district of Kottayam. The trend in area production, and yield were analysed using compound growth rate and percentage change over the previous year. The compound growth rate of area under rubber is found to be 8.2 per cent during the period 1950-51 to 2004-05. Although in absolute terms production has been increasing, there has been a decreasing trend since 1999-2000 till 2001-02. The compound growth rate of production comes to 16.36 per cent. The productivity of natural rubber recorded a continuous growth over the period except in 1999-2000 to 2001-02. The compound growth rate for yield works out to 7.47 per cent. A look into the global natural rubber scenario revealed that Thailand, Indonesia and Malaysia are the leading producers and they together constitute about 77 per cent of the global production. India is the fourth largest producer and consumer of natural rubber. China tops the list of consuming countries. The major exporters are Thailand, Indonesia and Malaysia and the major importers are China, USA and Japan. The analysis of the commodity derivatives market in India revealed that out of the three National Commodity Exchanges, National Multi Commodity exchange is the first exchange. All these three exchanges are multi commodity exchanges. The commodity exchanges are regulated by forward markets commission which is coming under the Ministry of Consumer Affairs, food and nutrition. To analyse the objective of examining the price movements of rubber futures through NMCE the co-integration technique is used. The results revealed that the futures prices of two months prior to delivery (F2) one month prior to delivery (F1) and delivery month (F0) are efficient in predicting the spot prices of rubber and prediction using futures price three months prior to delivery (F3) is not effective. The impact of futures trading on the farm management practices of the rubber farmers were analysed using simple percentages and averages. The study revealed that there is no change in any of the activity undertaken by the rubber farmers before and after commencement of futures trading. The non-trading farmers are enjoying the economics of large scale operations. Also the only positive change of the futures trading is their awareness about the storing facilities available at Central Warehousing Corporation eventhough they are not using that facility. The influence of private traders in marketing the product is as high as Rubber co-operative Marketing Society and Rubber Producers Society. No exploitation was faced by any of the farmers as they are educated farming community having better bargaining power. The futures trading could not make a considerable impact on the farming decisions of rubber farmers because they are not at all interested in delivery and so they are least bothered about the underlying asset. They consider futures trading as an avenue for speculation where they can bet on the price movements. For identifying the determinants of online trading by rubber farmers, Kendall’s coefficient of concordance was applied. Accessibility to trading terminal, awareness creation and computer literacy were found the most important determinants of futures trading. There are some differences in the ranks assigned by trading and non-trading members. Availability of warehousing facility, procedure formalities and speculative nature were found least important determinants. Starting of terminal outlets in remote areas, extensive campaign for awareness creation about futures trading and computer education to remove the aversion towards screen based trading will attract move number of participants to futures trading. Compulsory delivery of the underlying asset is to be enforced by the regulatory authorities to make the real farmers the beneficiaries of futures trading and thereby ensuring a remunerative price.